Análisis e interpretación de los estados financieros de la empresa "SUPER 1001" de la ciudad de Santo Domiongo de los Colorados, períodos 2006-2007 - Vallejo Ponce, Nelly Marlene (2016)
The so-called thesis: "Analysis and interpretation of the financial statements of the company "SUPER 1001"of the city of SANTO DOMINGO DE LOS TSÁCHILAS period 2006-2007", allows to comply with the proposed objectives and making reference to make the interpretation to the financial statements of the company "SUPER 1001" of the city of Santo Domingo de los Tsáchilas, period 2006-2007in order to provide reliable information for decision-making. Performing by vertical and horizontal financial statements analysis and interpretation, through the application of financial indexes. The financial situation was better in 2006, since it has liabilities totaling more heritage by the value of $985.996.89 having a difference with the year 2007 the value of $316.009.62, the results of the lack of capital in the year 2007, is that the owner of the company I use in available money that had as capital for the construction of a country house with recreation games. It is so for the year 2007 it does not have sufficient capital to invest in the company and thus to obtain a more representative value that was obtained. He is recommended to those who currently run the company "Súper 1001" that require the accountant, the application of financial analysis, so you can generate information that allows to know the financial and economic situation for the future of decisions promptly. Prepare and submit financial statements according to the regulations in force, in order to be at the level of the competition and avoid adverse contingencies, for breach of the provisions.